1986
DOI: 10.1063/1.450204
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the absorption spectra of complex pentavalent actinide halides: LiUF6, α-NaUF6, and CsUF6

Abstract: Absorption spectra of polycrystalline samples of LiUF6, α-NaUF6, and CsUF6 have been recorded at 4, 77, and 298 K. This group of compounds has a common sixfold U–F coordination that approaches an octahedral site symmetry for LiUF6 but exhibits increasing trigonal distortion (D3d symmetry) along the indicated series. Spectra have been systematically interpreted as consisting of sequences of vibronic transitions coupled to well-defined electronic excited states. Crystal-field calculations have been performed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
5
0

Year Published

1986
1986
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 27 publications
3
5
0
Order By: Relevance
“…The experimental spectra also exhibit peaks that were assigned to purely electronic transitions. As spectulated by Ryan and supported by CF calculations, the electronic magnetic-dipole intensity can be comparable to the vibronic intensities.…”
supporting
confidence: 60%
See 2 more Smart Citations
“…The experimental spectra also exhibit peaks that were assigned to purely electronic transitions. As spectulated by Ryan and supported by CF calculations, the electronic magnetic-dipole intensity can be comparable to the vibronic intensities.…”
supporting
confidence: 60%
“…Particular attention has been paid to UX 6 – . Because of the 5f 1 configuration, many of the associated properties can be understood based on a single-electron picture, and uranium is much more benign to work with than the neighboring actinides. The ground states (GSs) and the LF excited states (ESs) were characterized by electron paramagnetic resonance (EPR), near-infrared (NIR) absorption spectroscopy, ligand X-ray absorption spectroscopy, CF and LF theory, as well as molecular orbital and correlated wave function theory.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to [UCl 6 ] − there is a feature at 33 cm −1 that does not correspond to any vibrational frequency, therefore, it is not produced in the calculations. Similar explanations 68,69 as for the 23 cm −1 feature in [UCl 6 ] − apply here as well. The comparison of the calculated and measured spectra likewise show that fine structure details of the MCD can be assigned with the help of the calculations, but in some cases, even the signs of the vibronic peaks are challenging to obtain.…”
Section: Dalton Transactions Papersupporting
confidence: 72%
“…In the experimental spectrum, there is a shoulder to the first vibronic feature at 23 cm −1 which does not correspond to any vibrational frequency, therefore, it was not reproduced in the calculations. Hecht et al showed evidence that this feature could be due to coupling with an unassigned low energy mode, 68 while Ohwada attributed a similar feature to a rotational or translational lattice vibrational mode. 69 The sign, shape, and energy for all the fine structure features are well simulated with RAS-SO.…”
Section: Kk=jλ Hψmentioning
confidence: 99%